Advantages of delayed ventriculoperitoneal shunting in post haemorrhagic hydrocephalus seen in low birth weight infants - Taylor, Allan Grant (Division of Neurosurgery, 2018)
INTRODUCTION: The incidence of intraventricular hemorrhage (IVH) in very low birth weight infants is between 25 and 50%. Approximately 13-60% of these patients will develop progressive post hemorrhagic hydrocephalus (PHH) and of these 22- 70% will require CSF diversion. The most common therapeutic intervention is insertion of a ventriculoperitoneal shunt but there is considerable controversy surrounding the timing of the operation. Most authors promote early surgery to prevent secondary injury from hydrocephalus but it was our impression that this was associated with a higher incidence of shunt complications. METHOD: The incidence of shunt complications in 36 patients shunted for PHH were retrospectively reviewed. Patients were treated at Red Cross Children's Hospital over an 8 year period. RESULTS: Nine (25%) of the 36 patients required shunt revision for obstruction, seven required revision during the initial admission. Shunt infection occurred in 4 patients (11 %) all during the initial hospital admission. Four patients died, one from a shunt related complication. There was a clear relationship between the timing of surgery and the incidence of complications (chi square test p,0.01 ). Nineteen patients underwent surgery before 5 weeks of age and 9 developed early shunt complications. Of those shunted after 5 weeks none had an early complication. Groups were matched for weight and grade of IVH. DISCUSSION: A possible explanation for these results is that shunt complications are related to the quantity of blood present in the CSF at the time of shunting. A short delay before intervention is recommended in an effort to reduce the morbidity of shunt complications.